Distribution of Extended Spectrum Β-Lactamase Genes among Proteus Mirabilis Isolated From Clinical Specimens in Duhok City, Kurdistan Region, Iraq - Khalid, Haval M.; Yassin, Najim A. (Science Journal of University of Zakho, 2017)
Extended Spectrum Beta Lactamase-among Proteus mirabilis strains recorded high incidence leaving few therapeutic options of potential infections. The purpose of current study was to assess the prevalence of antibiotic resistance among Extended Spectrum Beta-Lactamases (ESBL) producing P. mirabilis, in addition to molecular characterization of the ESBL gene-types using PCR. All isolates were fully identified, checked for antibiotic susceptibility and ESBL production using double disk synergy phenotypic method. Positive ESBL-producing isolates were subjected to PCR assay using specific primers for detection of CTX-M, TEM, and SHV genes. The majority of the isolates exhibited absolute susceptibility (100%) to both meropenem and ertapenem and high susceptibility (95%) to imipenem, while co-resistance were expressed toward cefotaxime, ceftazidime, ceftriaxone and other non-lactam antibiotics. Out of 37 isolates, 21(57%) were ESBL-producers and using a double-disc synergy test (DDST). Using molecular-based PCR, CTX-M (81%), TEM (57%) and SHV (24%) were determined among ESBL-positive. CTX-M was predominant and circulating among phenotypic multiple resistant strains. Moreover, the coexistence of CTX-M and TEM gene was a more frequent combination. The study highlighted the increasing levels of low antibiotic susceptibility among P. mirabilis harbored ESBL genes at Duhok city and also confirms that a high level of blaCTX-M-positive ESBL isolates is circulating in this area.